Factors that influence the behavior of a person against the risk of starting a business in Latin America (Journal of Business, Universidad del Pacífico (Lima, Peru), 2016)
Unemployment and low quality jobs have created the need to undertake and move from being an employee to an entrepreneur. However, there are some factors that characterize this behavior. This research identifies some of the factors that increase a person's risk of starting a business in Latin America. The main factors that influence this behavior are: experience, knowledge, skill and age among the eleven variables used in the 2009-2011 period. The neural network models used classify the dependent variable (fear of failure) with a success rate of 68% in the study period.
Keywords: Risk factors; entrepreneurship; artificial neural networks; behavior; Latin America